An enhanced 1-round authentication protocol for wireless body area networks with user anonymity. (July 2017) - Li, Xiong; Peng, Jieyao; Kumari, Saru; Wu, Fan; Karuppiah, Marimuthu; Raymond Choo, Kim-Kwang
Highlights: We point out the security weaknesses of Liu et al.'s lightweight authentication protocol for wireless body area networks. We propose an enhanced 1-round authentication protocol for wireless body area networks with user anonymity. We evaluate the security features of the proposed protocol using formal analysis based on BAN logic and informal analysis. The comparison results show that our protocol improves the security with equivalent cost. Graphical abstract: Abstract: The Wireless Body Area Networks (WBAN) emerges with the development of wearable devices and medical sensors, which can be used in healthcare monitoring to improve the quality of medical services. The data collected by WBAN usually be transmitted via wireless channel, and includes some sensitive information of the patients'. Therefore, how to design light-weight security protocols for WBAN with resource-constrained devices is a tough challenge. Recently, Liu et al. presented a lightweight authentication protocol for WBAN with less computation and communication cost. However, some weaknesses of this protocol are found through security analysis. In this paper, an improved single-round authentication protocol is proposed to remove the flaws of previous work. Meanwhile, the formal and informal security analysis of our protocol are discussed. The comparison results show that our protocol improves the security with equivalent cost.